Facts & figures : - Ackert, Patricia (Thomson, 2005)
Through wonderful readings and carefully designed activities, this best-selling series helps students develop reading skills and systematically increase their active vocabulary. Learners develop useful and relevant vocabulary while exploring and expanding critical thinking skills.